Les hernies internes étranglées dans les cliniques universitaires de chirurgie viscérale A et B du CNHU HKM de Cotonou de 1998 à 2009 - GBESSI, GASPARD DANSOU; OLORY-TOGBE, JEAN-LÉON TOUSSAINT; DOSSOU, FRANCIS MOÏSE DJIDÉNOU; HOUNKPE, PIERRE-CLAVER; MENSAH, E.; LOKOSSOU, THOMAS COMLAN; BAGNAN, KÉMOKO OSSÉNI; PADANOU, NAZAIRE (My University, 2012)
71 Rev. Afr. Anesth. Med. Urg. X 1., <1,2012 AB5TRACT rreducible to pass througn a hale or several depressions of the abdominal cavity, internai hernias are strangulated bowel obstruction discovered during laparotomy. Objectives: - Identify internai hernias, - Ta study the circumstances of diagnosis, - Assess their management. Patients and lVlethod : This is a retrospective study over a period of 12 years tram January, 1998 ta Decernber, 2009 in the university clinics of Visceral Surgery A and 8-HKM CNHU otonou. esults_: Three cases of internai hernias ;:Jre listed str,mgled over <:1 period of 12 years. he disease had affected the patients of both sexes: two men and one woman. The patients ere young and 19 vears o/d, 23 ye<lrs and 25 years. Patients admitted ta the emergency showed diffuse abdominal pain for ov~r four days with progressive abdominal distension. The radiographs of th~ abdomen without prepëlr<Jtion S owed air-fil/id leveis secn a srnall bowel obstruction. The median l<Jparotomies stradclles the umbilicus found 3 cases of internai hernia ~trangulation: two cases of para duodenal hernia right and one case of intestinal herniation fomentai foramen. There was intestinal necrosis. ~he surgery was bowel resection followed by end to end anastornosis. The postoperative ourses are simple in 3 cases. Conclusion: Internai hernias are rare in CNHU HKM Cotonou, The diagnosis is late and there 5 necrosis of intestinalloo
Keywords: hernies internes étranglées; fréquence; complications